Cytogenetic and Random Amplified Polymorphism Dna Analysis of Subspecies of Asian Elephants (Elephas Maximus) - Sharudin, Samsul Bariah (2005)
A study was carried out to investigate the chromosome constitution of 3 subspecies of elephants from cultured lymphocytes; karyotypes were constructed according to standard procedure. Lymphocytes were cultured in RPMI 1640 medium supplemented with a mitogen (phytohemagglutinin-PHA or pokeweed-PWM), penicillin- streptomycin and bovine calf serum. The karyotype showed that the Asian elephant has a diploid number (2n) of 56 and fundamental number (NF) of 66 in both male and female. The autosomes comprised 6 pairs of submetacentric, 10 pairs of large acrocentric and the remaining 11 pairs are characterized as small acrocentric. On the other hand, the sex chromosomes consisted of the largest submetacentric X chromosome while the Y chromosome is a small acrocentric.G-, C- and NORs bandings were carried out to assist the conventional banding. Gbanded karyotypes of the three subspecies were identical as well as for the C- banded karyotypes. NORs banding revealed active nucleolar organizer regions chromosomes 2, 4, 13 and 17. These results were the first banded karyotypes established for the Asian elephants. Investigations of DNA polymorphisms using RAPD technique provided identical information between the three subspecies. Blood samples from three subspecies of the Asian elephants were employed in the study. Based on band sharing frequency value of pair-wise comparison within subspecies, the genetic relationship between Malayan and Indian elephants was determined to be low and likewise between the Indian and Myanmar elephants. Interestingly, the band sharing frequency value between Malayan elephant and Myanmar elephant are genetically closely similar to the Malayan elephants compared with the Indian elephants. With regards to the similarities in chromosome morphology as well as at the DNA level, they are able to breed amongst themselves without any complication related to parental chromosomal incompatibility.